2015
DOI: 10.1101/032763
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Early farmers from across Europe directly descended from Neolithic Aegeans

Abstract: Farming and sedentism first appear in southwest Asia during the early Holocene and later spread to neighboring regions, including Europe, along multiple dispersal routes. Conspicuous uncertainties remain about the relative roles of migration, cultural diffusion and admixture with local foragers in the early Neolithisation of Europe. Here we present paleogenomic data for five Neolithic individuals from northwestern Turkey and northern Greece -spanning the time and region of the earliest spread of farming into E… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
166
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2
1

Relationship

5
4

Authors

Journals

citations
Cited by 101 publications
(179 citation statements)
references
References 27 publications
10
166
1
1
Order By: Relevance
“…18) and no population structure in any of the four groups. 5 Moreover, the panmictic population model proposed would need to be compared against alternatives (eg, ref. 11).…”
Section: Resultsmentioning
confidence: 99%
“…18) and no population structure in any of the four groups. 5 Moreover, the panmictic population model proposed would need to be compared against alternatives (eg, ref. 11).…”
Section: Resultsmentioning
confidence: 99%
“…145 We also generated 62 new direct radiocarbon dates (Extended Data Bronze Age Britain. We combined our data with previously published ancient DNA data [2][3][4][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37] 150 to form a genome-wide dataset of 476 ancient individuals (Supplementary Table 1). The 151 combined dataset included Beaker-associated individuals from Iberia (n=20), southern France 152 (n=4), northern Italy (n=1), central Europe (n=56), The Netherlands (n=9) and Britain (n=19).…”
mentioning
confidence: 99%
“…The analysis of north-western Anatolian Neolithic samples from the Marmara region in Turkey (Mathieson et al 2015), which also clearly cluster within the ancient Europeans' Neolithic pool, confirmed that the source of the agricultural incomers reached Europe through northern Anatolia, and probably followed a route across Greece to Europe (Hofmanová et al 2016).…”
Section: Further Readingmentioning
confidence: 66%
“…The admixture with local hunter-gatherers increased substantially at later stages (Haak et al 2015;Hofmanová et al 2016) at the transition to the Middle Neolithic across Europe, while Late Neolithic and Bronze Age periods were characterised by increasing input from steppe populations (Haak et al 2015).…”
Section: Further Readingmentioning
confidence: 99%